Incentives for deforestation-free value chains in the Peruvian Amazon - Tristán Febres, María Claudia; Ivanova, Yovita; Quintero, Marcela (2022)
This article has the following objectives: 1) to identify the bottlenecks in the cocoa and palm oil value chains in the Ucayali region (Peru), so that their different actors and links can contribute to avoid deforestation, and 2) based on these bottlenecks, to identify the enabling conditions and incentives (from the perspective of the actors in the different links of these value chains), necessary to reduce or avoid deforestation in this Amazon region.